Inovasi pengolahan limbah plastik menjadi produk paving block sebagai upaya pelestarian lingkungan di Desa Pablengan - Erwinda Sam Anafih; Dwi Cahyono; Fitri Dianitami; Dito Anggita; Riski Bayu Setiawan; Adimas Putra; Syifa Ramadhani; Rindra Jaka; Iwan Ramadhani (Penamas: Journal of Community Service, 2026)
The problem of plastic waste management in Pablengan Village is triggered by the lack of a final disposal site (TPA) and the practice of open burning. This community service activity aims to convert plastic waste into paving blocks by mentoring the Karang Taruna (Youth Group) and local village officials as primary partners. Methods used included observation, participatory discussions, and technical production training. The activity results showed an increase in partners’ understanding of waste management from 35% to 85%, based on pre- and post-test results. The training involved 25 participants and resulted in the production of 50 prototype paving blocks utilising approximately 40 kg of plastic waste. This implementation has the potential to sustainably reduce plastic waste in the village while creating new economic opportunities. This program successfully transformed an environmental burden into functional infrastructure materials for the village.